Surrogate End Points for Overall Survival in Loco-Regionally Advanced Nasopharyngeal Carcinoma: An Individual Patient Data Meta-analysis. (17th December 2016) - Rotolo, Federico; Pignon, Jean-Pierre; Bourhis, Jean; Marguet, Sophie; Leclercq, Julie; Tong Ng, Wai; Ma, Jun; Chan, Anthony T. C.; Huang, Pei-Yu; Zhu, Guopei; Chua, Daniel T. T.; Chen, Yong; et al.
Abstract : Background: Our objective was to evaluate progression-free survival (PFS) and distant metastasis–free survival (DMFS) as surrogate end points for overall survival (OS) in randomized trials of chemotherapy in loco-regionally advanced nasopharyngeal carcinomas (NPCs). Methods: Individual patient data were obtained from 19 trials of the updated Meta-Analysis of Chemotherapy in Nasopharyngeal Carcinoma (MAC-NPC) plus one additional trial (total = 5144 patients). Surrogacy was evaluated at the individual level using a rank correlation coefficient ρ and at the trial level using a correlation coefficient R 2 between treatment effects on the surrogate end point and OS. A sensitivity analysis was performed with two-year PFS/DMFS and five-year OS. Results: PFS was strongly correlated with OS at the individual level ( ρ = 0.93, 95% confidence interval [CI] = 0.93 to 0.94) and at the trial level ( R 2 = 0.95, 95% CI = 0.47 to 1.00). For DMFS, too, the individual-level correlation with OS was strong ( ρ = 0.98, 95% CI = 0.98 to 0.98); at trial level, the correlation was high but the regression adjusted for measurement error could not be computed (unadjusted R 2 = 0.96, 95% CI = 0.94 to 0.99). In the sensitivity analysis, two-year PFS was highly correlated with five-year OS at the individual level ( ρ = 0.89, 95% CI = 0.88 to 0.90) and at the trial level ( R 2 = 0.85, 95% CI = 0.46 to 1.00); two-year DMFS was highly correlated with five-year OS at the individual level ( ρ = 0.95, 95% CI = 0.94 to 0.95) and at the trial level ( R 2 = 0.78, 95% CI = 0.33 to 1.00). Conclusions: PFS and DMFS are valid surrogate end points for OS to assess treatment effect of chemotherapy in loco-regionally advanced NPC, while PFS can be measured earlier.